Efektivitas Pelatihan Penanggulangan Bencana Gempa Bumi Terhadap Pengetahuan Kesiapsiagaan Guru Sekolah Dasar Kota Palu - Lusia Salmawati; Pertiwi Pertiwi; Marselina Marselina (Universitas Pahlawan Tuanku Tambusai, 2025)
Disaster is known as a natural, unnatural, or man-made event that threatens and causes losses to people's lives and livelihoods, including loss of life, environmental damage, property loss, and psychological effects. The purpose of this study is to determine the effectiveness of earthquake prevention training in elementary school teacher training in Palu City. The purpose of this study is to determine the effectiveness of earthquake prevention training in elementary school teacher training in Palu City. This study uses a quantitative research type with a pseudo-experimental approach. This study will be conducted in 9 elementary schools in the Palu City area. All participants in this study are teachers from the Palu City area. The population in this study amounted to 170 people using the Purposive Non Random Sampling Technique with sample determination based on high-risk areas for earthquakes. Data analysis used consisted of descriptive and hypothetical with the paired sample t-test. The results of the study found that from the four sub-districts, elementary school teachers in East Palu sub-district showed that knowledge (sig. (2-taileid) = 0.000), attitude (sig. (2-taileid) = 0.000), emergency response planning (sig. (2-taileid) = 0.000) and resource mobilization (sig. (2-taileid) = 0.000), had a significant influence on the preparedness of elementary school teachers in East Palu sub-district compared to teachers in other sub-districts. Elementary school teachers in East Palu sub-district are required to create a program to improve their ability to deal with disasters and instill disaster knowledge in students as early as possible and to continue to balance the program for elementary school teachers to improve their skills and abilities in preventing disasters.